2015
DOI: 10.1371/journal.pone.0139854
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Very Low Dose Fast Neutrons on Cell Membrane And Secondary Protein Structure in Rat Erythrocytes

Abstract: The effects of ionizing radiation on biological cells have been reported in several literatures. Most of them were mainly concerned with doses greater than 0.01 Gy and were also concerned with gamma rays. On the other hand, the studies on very low dose fast neutrons (VLDFN) are rare. In this study, we have investigated the effects of VLDFN on cell membrane and protein secondary structure of rat erythrocytes. Twelve female Wistar rats were irradiated with neutrons of total dose 0.009 Gy (241Am-Be, 0.2 mGy/h) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 53 publications
0
21
0
1
Order By: Relevance
“…Although DNA damage and repair products have been identified as significantly increased with neutrons, whether that is assessed with micronuclei (22), comet assay (39) or chromosomal changes (40, 41), small molecules associated with such a process or DNA repair were not identified in the biofluids through a global LC-MS approach. The exception was uric acid, which was previously identified in higher levels in urine of exposed mice (42) and humans (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although DNA damage and repair products have been identified as significantly increased with neutrons, whether that is assessed with micronuclei (22), comet assay (39) or chromosomal changes (40, 41), small molecules associated with such a process or DNA repair were not identified in the biofluids through a global LC-MS approach. The exception was uric acid, which was previously identified in higher levels in urine of exposed mice (42) and humans (12).…”
Section: Discussionmentioning
confidence: 99%
“…Early decrease of fatty acids, such as arachidonic acid, can be attributed directly to increased oxidative stress, which can lead to lipid peroxidation and protein alterations (43, 44). In addition, others have shown that membrane fluidity is decreased even with low doses of neutrons (0.9 cGy) and decreased lipid-to-protein ratios in membranes may be a consequence of increased lipid peroxidation and degradation (39). Changes in membrane solubilization and osmotic fragility after exposure to fast neutrons were also observed in erythrocytes (45).…”
Section: Discussionmentioning
confidence: 99%
“…1 and 2 and Tables 1 and 2). This suggests lipid oxidation and saturation of the double bonds (Saeed et al, 2015). Low radioresilience of these bonds follows from their high chemical reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is a controversy over the cellular responses following exposure to low doses of ionizing radiation [15]. Substantial data indicate that exposure to ionizing radiation can lead to the induction of oxidative stress in plants [16], animals [17,18], and humans [19]. On the other hand, it has been shown that low doses of ionizing radiation may cause some bio-positive effects through preventing oxidative stress [20][21][22].…”
Section: Ionizing Radiationmentioning
confidence: 99%